Continuity of care in the transition from child to adult diabetes services: a realistic evaluation study - Samantha Groves (Journal of Health Services Research & Policy, 2012)
OBJECTIVES: To identify the continuity mechanisms central to a smooth transition from child to adult diabetes care, the service components through which these can be achieved and their inter-relations in different contexts.METHODS: A realistic evaluation study of five models of transition in England comprising: organizational analysis (semi-structured interviews with 38 health care professionals and selected observations); case studies of 46 young people under-going transition and 39 carers (three qualitative interviews over a 12-18 month period, medical record review and clinical interviews); surveys of 82 (32% response rate at least once and 11% response rate at two time points) young people in the population approaching, undergoing or less than 12 months post-transition, and their carers (questionnaires included psychosocial outcome measures); and a costs and consequences analysis.RESULTS: Seven continuities contribute to smooth transition: relational, longitudinal, management, informational, flexible, developmental and cultural. Relational, longitudinal, flexible and cultural continuity are the most important. Models with high levels of relational, longitudinal, flexible and cultural continuity achieve smooth transition with relatively informal, low-cost informational and management continuity mechanisms. Models with low levels of relational and longitudinal continuity need to invest in more formal interventions to facilitate management, flexible and informational continuity so that smooth transition is not compromised.CONCLUSIONS: Focusing on continuity mechanisms, their inter-relations and the effectiveness of different constellations of service components in achieving smooth transition has furnished evidence to inform the development of innovative models which build on the logic of these findings but are sensitive to local context. Further studies are needed to confirm the quantitative findings from a broader range of services and patients.